2012
DOI: 10.1038/eye.2012.3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy equity profile in a multi-ethnic, deprived population in Northern England

Abstract: Purpose Equity profiles are an established public health tool used to systematically identify and address inequity within health and health services. Our aim was to conduct an equity profile to identify inequity in eye health across Leeds and Bradford. This paper presents results of findings for diabetic retinopathy in Bradford and Airedale. Methods A variety of routine health data were included and sub-analysed by measures of equity, including age, sex, ethnicity, and deprivation to identify inequity in eye h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 2 publications
1
24
0
Order By: Relevance
“…49 There is considerable evidence that SES may determine the risk for diabetic eye complications, such as retinopathy, that ultimately have an impact on quality of life. 14,20,29 Our findings support previous research that income is a predictor of visual impairment among patients with diabetes. 29 However, the causal link between income and eye complication is still unclear.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…49 There is considerable evidence that SES may determine the risk for diabetic eye complications, such as retinopathy, that ultimately have an impact on quality of life. 14,20,29 Our findings support previous research that income is a predictor of visual impairment among patients with diabetes. 29 However, the causal link between income and eye complication is still unclear.…”
Section: Resultssupporting
confidence: 93%
“…Similarly, under the universal health care system in the United Kingdom, the rate of DR screening was significantly lower in patients residing in deprived areas. 15,20,21 Because there is a strong socioeconomic health gradient, 22 and use of ophthalmic clinical care is less frequent in patients with lower SES, it would follow that lower SES is also a key predictor of increased rates of diabetic eye complications. 12,20,[23][24][25][26][27][28] Accordingly, Brown et al 29 found that lower SES, as measured by individual or household income, education, employment, occupation, or living in an underprivileged area, was associated with increased risk for microvascular disease, including diabetic eye complications.…”
mentioning
confidence: 98%
“…Findings from a health equity audit from Leeds supported these results and also identified fewer optometry practices in areas of high deprivation 22. Similar disparities between health needs and health services were found for diabetic retinopathy 23. The Tudor Hart inverse care law states that availability of good medical care tends to vary inversely with the need of the population, particularly where medical care is exposed to market forces 32.…”
Section: Discussionmentioning
confidence: 73%
“…Patients’ lack of awareness, psychological factors (fear and guilt), or practical obstacles, such as obtaining time off work, were also important 9. Patients living in the most deprived areas were less likely to attend for screening while having worse retinopathy 10,11. Uptake rates in the same area can vary between practices from 55% to 95%; practices can have a higher, or lower, uptake rate than suggested by their patient population 12.…”
Section: Introductionmentioning
confidence: 99%